STUDENT CREATION PROCESS IN MAKING BASIC TWO-DIMENSIONAL ART AND DESIGN ASSIGNMENTS BY DIGITAL METHODS - Niken Larasati Ayuningtyas; Nedina Sari (Gorga : Jurnal Seni Rupa, 2024)
Basic Two-Dimensional Art and Design is one of the mandatory courses taught at fine arts and design colleges, including at the Bandung Institute of Technology (ITB). This course aims to train student™ sensitivity to processing basic shapes or forms and technical skills in using traditional tools such as colored pencils and poster paints. However, with the developmnet of digital technology and since the Covid-19 pandemic, which required students at that time to carry out the learning process online, the majority of students switched to using graphic software in making assignments, especially in field composition tasks. Therefore, this study aims to explore the stages of students in making field composition assignments in a digital way and analyze the suitability of the results of the assignment with the achievements of this course. The research method used is participatory observation, where the author acts as a student assistant in the course, as well as conducting interviews with lecturers and three students who re-practice how to make field composition assignments. The results of the analysis revealed variations in visual complexity and design approaches between students who used conventional and digital methods. Students create field composition assignments using laptops and tablets whose creation process is carried out at their respective homes, not in the classroom. These findings provide insight into the adaptation of the fine arts education curriculum to digital technology, as well as highlight the importance of technology integration in art learning in response to the development of the times and the changing preferences of students towards creative tools and media.KEYWORDSCreation, Basic Form, Two-Dimensional AUTHORSNiken Larasati AyuningtyasNedina Sari REFERENCESBudiwirman, B., Syeilendra, S., Ramadhan, A., & Syafei, S. (2023). Seni Tradisional Dalam Seni Musik Modren: Analisis Berdasarkan Nilai Pendidikan. Gorga¯: Jurnal Seni Rupa, 12(1), 108-115. https://doi.org/10.24114/gr.v12i1.27135Dewi, N. K. (2023). Analisis Kemampuan Mendesain Poster Bertema Seni Budaya Ntb Pada Mahasiswa Calon Guru Sekolah Dasar. Gorga ¯: Jurnal Seni Rupa, 12(1), 84-90. https://doi.org/10.24114/gr.v12i1.43654Elpalina, S., Ambiyar, A., Agustina, A., & Azis, A. C. K. (2024). Implementasi Model Evaluasi Formatif-Sumatif Dalam Meningkatkan Pembelajaran Seni Budaya. Gorga : Jurnal Seni Rupa, 13(1), 1“8. https://doi.org/10.24114/gr.v13i01.55826Hendriyana, H. (2019). Rupa Dasar Nirmana Asas dan Prinsip Dasar Seni Visual. Penerbit Andi.Hendriyana, H. (2022). Rupa Dasar Nirmana Asas dan Prinsip Dasar Seni Visual. Penerbit Andi.Kembaren, Y. A., Kartono, G., & Mesra, M. (2020). Analisis Karya Poster Berdasarkan Unity, Layout, Tipografi, Dan Warna. Gorga¯: Jurnal Seni Rupa, 9(1), 121. https://doi.org/10.24114/gr.v9i1.18187Mubarat, & Ilhaq. (2021). Telaah Nirmana sebagai Proses Kreatif Dalam Dinamika Estetika Visual. Ekspresi Seni: Jurnal Ilmu Pengetahuan dan Karya Seni, 23(1), 125“139. http://journal.isi-padangpanjang.ac.id/index.php/Ekspresi/article/view/397Munawar, Z., Herdiana, Y., Suharya, Y., & Indah Putri, N. (2021). Pemanfaatan Teknologi Digital Di Masa Pandemi Covid-19. Tematik, 8(2), 160“175. https://doi.org/10.38204/tematik.v8i2.689Pratama, R. E., & Mulyati, S. (2020). Pembelajaran Daring dan Luring pada Masa Pandemi Covid-19. Gagasan Pendidikan Indonesia, 1(2), 49. https://doi.org/10.30870/gpi.v1i2.9405Sanyoto, S. E., & Widada, R. (2009). Nirmana: Dasar-Dasar Seni dan Desain. Jalasutra.Sugiyono. (2012). Metode Penelitian Kombinasi (Mixed Methods). Alfabeta.Sulistiya, M., Mu™afi, Z., Natasia, S. R., Herlina, H., & Yusuf, M. (2021). Penerapan Metode Think Aloud untuk Evaluasi Usability pada Website Dinas Pendidikan dan Kebudayaan Kota MNO. Jurnal Telematika, 16(1), 25“32.Supandi, M. B., & Azis, A. C. K. (2020). Peninjauan Poster dari Warna Dan Tipografi di SMK Multimedia Istiqlal. Gorga¯: Jurnal Seni Rupa, 9(2), 419. https://doi.org/10.24114/gr.v9i2.21236Tabrani, P. (2000). Proses Kreasi, Apresiasi, Belajar. Penerbit ITB.Tabrani, P. (2023). Potensi Manusia: Kreativitas (IV). ITB Press.